2020
DOI: 10.1371/journal.pmed.1003086
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive use among adolescent and young women in North and South Kivu, Democratic Republic of the Congo: A cross-sectional population-based survey

Abstract: Background Adolescent girls in humanitarian settings are especially vulnerable as their support systems are often disrupted. More than 20 years of violence in the Democratic Republic of the Congo (DRC) has weakened the health system, resulting in poor sexual and reproductive health (SRH) outcomes for women. Little evidence on adolescent contraceptive use in humanitarian settings is available. CARE, International Rescue Committee (IRC), and Save the Children, in collaboration with the Reproductive Health Access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 35 publications
9
49
0
2
Order By: Relevance
“…This study investigated the factors in uencing modern contraceptive utilisation among single mothers. The study differs from existing studies that focused on other segments of childbearing women such as adolescents [21][22][23], never married women [24][25][26] and women of advanced reproductive age [27][28][29][30] by focusing on single mothers. This group of women has received little attention in family planning programming in Nigeria.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This study investigated the factors in uencing modern contraceptive utilisation among single mothers. The study differs from existing studies that focused on other segments of childbearing women such as adolescents [21][22][23], never married women [24][25][26] and women of advanced reproductive age [27][28][29][30] by focusing on single mothers. This group of women has received little attention in family planning programming in Nigeria.…”
Section: Discussionmentioning
confidence: 88%
“…Existing studies in Nigeria and elsewhere have examined the associated factors of modern contraceptive utilisation among different segments of women such as adolescents and young people [21][22][23], never married women [24][25][26], women of advanced reproductive age [27][28][29][30]. Other studies have focused the general population of childbearing women [31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…The independent variables were selected based on a review of the literature on FP and the availability of the variables in the dataset. They included the county of residence (Nairobi, Bungoma, Kericho, Kiambu, Kili , Kitui, Nandi, Nyamira, Siaya, Kakamega and West Pokot), residence (rural/urban) [20,21], age in years (15-19, 20-34 and 35-49) [21], education levels (no formal, primary, secondary and tertiary) [21][22][23], wealth quintiles (poorest, poorer, middle, richer, richest) [20], parity (0, 1, 2-3 and 4+) [23], desire for more children (yes/no/infertile) [24], and age at sexual debut in years [25].…”
Section: Data Source and Study Populationmentioning
confidence: 99%
“…The program underwent periodic monitoring and evaluation reviews, including client satisfaction surveys, register reviews, and scienti c studies, which were presented at international venues, published in peer-reviewed journals, or both [12][13][14][15][16][17]. Results from these studies showed the overall feasibility of FP and PAC programs in mostly protracted crisis humanitarian settings (with an acute phase due to the Ebola outbreak in the DRC), a high level of acceptability by clients above 90% [14], and the shift from the harmful practice of dilatation and curettage to manual vacuum aspiration or medication use for the provision of PAC [12].…”
Section: Interventionmentioning
confidence: 99%